Happiness or Eudaimonia? A Critical Review on the Book The Politics of Happiness: What Government Can Learn from the New Research on Well-Being - Seyedmohsen Alavipour (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Throughout different civilizations and cultures, political philosophers have contemplated on the meaning of “happiness” as the goal of human life, and so, their contemplation has extended to the normative and policy-making domain of the ideal political state. However, while classically philosophers tended to understand the term as a quality for the good life, in the modern era the quantitative explanation of the subject prevailed and the goal alternated into human satisfaction through capital accumulation and economic growth. Nevertheless, modern social abnormalities, such as Opium, depression, and tremendous family break-ups led the socio-political intellectuals to explore alternatives that might help to find real, sustainable satisfaction in human social life. Among others, Derek Bok’s “Politics of Happiness” is an exploration for such alternative which is based on Buhtan’s national policy towards substitution of “happiness” for “economic growth” and attempts to indicate different elements and aspects of such transformation in social policies in western states, namely the United States.